2017
DOI: 10.3171/2016.9.spine16618
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and treatment outcomes of spinal epidural arteriovenous fistulas

Abstract: OBJECTIVESpinal epidural arteriovenous fistulas (SEDAVFs) constitute a rare but treatable cause of vascular myelopathy and are a different subtype from the more common Type I spinal dural AVFs. The purpose of this study was to review a consecutive series of SEDAVFs from a single institution and report on the clinical presentations, functional status, and treatment outcomes.METHODSThe authors identified all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…On the contrary, primary surgical treatment is less frequently undergone for the SEAVFs. 15 Interruption of the intradural draining vein can cause remnant of epidural AVF, and recruitment of the retrograde intradural drainage may occur via radiculomedullary vein at another spinal level. 16 Surgical approach to the arterized venous pouch has a risk of massive bleeding, and it is difficult because the venous pouch is usually located at ventral epidural space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, primary surgical treatment is less frequently undergone for the SEAVFs. 15 Interruption of the intradural draining vein can cause remnant of epidural AVF, and recruitment of the retrograde intradural drainage may occur via radiculomedullary vein at another spinal level. 16 Surgical approach to the arterized venous pouch has a risk of massive bleeding, and it is difficult because the venous pouch is usually located at ventral epidural space.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, endovascular technique is preferred to use for the treatment of SEAVFs in resent reports. 9 , 10 , 15 Nasr et al 15 recently reported a case series of SEAVF at a single center. In their series, 18 of 24 patients (75%) were treated by endovascular technique, 4 (16.7%) by open surgery, and 2 (8.3%) by combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…These lesions can result in considerable morbidity from congestive myelopathy secondary to chronic venous hypertension. [1][2][3][4][5][6] Delay in the identification of spinal vascular malformations has been shown to result in high rates of irreversible morbidity due to the natural history of the disease, unnecessary surgeries including spinal cord biopsies and laminectomies, costly-yet-ineffective medical interventions including intravenous immunoglobulin therapy, and substantial costs from unnecessary serologic and imaging investigations. 7 Once the imaging findings suggestive of a spinal vascular malformation are properly identified, further investigations are required to characterize the angioarchitecture and location of the dominant arterial feeders to the lesion.…”
mentioning
confidence: 99%
“…According to previous studies, TAE was more frequently selected for SEAVF patients compared with direct surgery, and favorable results were obtained by sufficiently injecting liquid embolic materials, such as NBCA or Onyx, into the intradural vein via the venous pouch. 1,[4][5][6] In particular, Kiyosue et al reviewed TAE of SEAVFs and reported that the occlusion rate of TAE was low when drainage involved epidural outflow, whereas it was 90% in patients with intradural reflux alone. 4) These studies indicated that a shunt was present on the ventral side of the spinal canal in many patients with SEAVFs, making direct surgery to the shunt difficult and that shunts remained after blockage of a vein with intradural reflux alone, inducing recurrent intradural drainage.…”
Section: Resultsmentioning
confidence: 99%